KAJIAN MANAJEMEN RISIKO PROYEK EKSPLORASI DAN PELAYANAN AIR BERSIH - Bakar, Abu; Yuniati, Yoanita; Rashif, Muhammad Zharfan (Inaque : Journal of Industrial and Quality Engineering, 2020)
The exploration and service of clean water through deep ground water drilling projects is a high-risk job that may be required risk control, such as risk to: time, cost, and quality. Risk a project that did not managed well can impact the loss of profits from the project being worked on and the loss of the next project opportunity. A step the management of risks are identification variable and risk indicators projects up through a literature study and interviews with experts, variable and risk indicators analysis critical in projects up through field research, the determination of highest risk by testing statistics, and do response to any risk project. The results showed that the three indicators that had the highest risk from the Exploration and Water service clean water project through deep ground water drilling were: pilot hole process, undoing the reaming hole process, and the obstacles pipeline entry process. The results of the analysis of the three indicators are proposed to mitigate the risks that need to be done, such as soil texture at project site, need for equipment backup, and related equipment reliability, a warehouse officer is required when mobilization to be equipped with a checklist of equipment to ensure that equipment is actually the use of either the amount, type, or condition of the equipment.